Pendampingan dan Sosialisasi Pembuatan Lumpia Durian dengan Metode ABCD (Asset Based Community Development) Sebagai Upaya Pemberdayaan Ekonomi Masyarakat - Annas; Wali Ramadhani; Miftahul Maula; Miftahul Jannah; Raisatunnisak; Sitti Adisa; Silvia Wulandari (Malik Al-Shalih : Jurnal Pengabdian Masyarakat, 2023)
Economic development is one of the efforts to improve the community and village economy. One of the efforts to improve the economy is entrepreneurship in various ways. One of them is the manufacture of durian spring rolls which was developed in Paya Bili Dua Village. This assistance was carried out by KKN students at the Langsa State Islamic Institute. The goal is to improve the welfare and income of the village community individually and as a community through the ABCD (Assed Based Community Development) method—service data based on observations and interviews. The result of this dedication is a natural asset in the form of durian which is modified into lumpia durian. This assistance is through training on how to make lumpia durian, and process and market them, both traditional and modern through social media. This is done so that the community can manage existing natural assets effectively, efficiently, and modernly.